ANALISIS STRATEGIS PROGRAM CSR PT SAMPOERNA AGRO TBK DALAM MENINGGKATKAN DAYA SAING PERUSAHAAN - , Hendra ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Corporate social responsibility (CSR) is commonly known as charitable activities conducted by a company as part of its responsibility for surrounding society which directly or indirectly were impacted by its operational activities. CSR is also included in government regulation thus resulting in a growing concern from the business people that CSR is weighting their budget and reducing their profit. Despite the negative perception about CSR, Porter and Kramer (2006), explained that if a company could manage the CSR activities in a smart way, they could bring opportunities, innovations and competitive advantages for the company. This research is conducted at PT. Sampoerna Agro Tbk. (SGRO) by incorporating three analysis tools: weighted factors analysis, Strategic CSR Program analysis and gap analysis, to see whether CSR activities at SGRO has a strategic impact for the company. This research shows that CSR program implementation at SGRO has yet brought no significant strategic impact for the company, mainly due to planned activity programs that misrepresented the initial visions so the reality did not meet the initially planned visions.